Chelation controlled regiospecific O-substitution of myo-inositol orthoesters: convenient access to orthogonally protected myo-inositol derivatives - Devaraj, Subramanian; Shashidhar, M. S.; Dixit, Shailesh S. (Tetrahedron, 2005)
A general method for the completely regioselective protection of the three secondary hydroxyl groups of orthoester derivatives of myo-mositol, utilizing the subtle differences in reactivity exhibited by its alkali metal alkoxides due to differences in their ability to form chelates, is described. This method provides convenient access to orthogonally protected myo-inositol derivatives. A comparison of the methylation of racemic 4-0-trityl-myo-inositol 1,3,5-orthoformate in the presence of sodium or lithium ions showed that stabilization of the C4-alkoxide by chelation with lithium overrides steric hindrance offered by the C6-axial substituent in deciding the regioselectivity during the nucleophilic O-substitution. (C) 2004 Elsevier Ltd. All rights reserved.

Cyclitol based metal complexing agents. preference for the extraction of lithium by myo-inositol based crown-4-ethers depends on the relative orientation of crown ether oxygen atoms - Dixit, Shailesh S.; Shashidhar, M. S.; Devaraj, Subramanian (Tetrahedron, 2006)
myo-Inositol derived crown-4-ethers in which two of the oxygen atoms in the crown ether moiety have different relative orientations were prepared. Metal picrate binding studies revealed that the crown ether having 1,3-diaxial orientation shows the highest selectivity for binding to lithium although the crown ether having 1,2-diequatorial orientation exhibited the highest binding constant for lithium picrate. These results suggest that relative binding affinity of metal ions to crown ethers can be tuned by varying the relative orientation of crown ether oxygen atoms. The relevance of these results to the previously observed regioselectivity during the O-substitution of myo-inositol orthoesters is discussed. (c) 2606 Elsevier Ltd. All rights reserved.
Keywords: crown ether; Cyclitol; Inositol; ligand; lithium; metal complex